The Wayward Bus movie still. - Charles G. Clarke:::Creator::::::::::::
The Wayward Bus movie still. Mildred Pritchard (Dolores Michaels) sitting with Johnny Chicoy (Rick Jason) in barn hay. RESTRICTED USE